Medical vocabulary in the dilogy of I. Ilf and E. Petrov "Twelve chairs" and "Golden Calf" - Zav'yalov, Viktor Nikolaevich; Sidorova, Alevtina YUr'evna (Филология: научные исследования, 2024)
The relationship between medicine and literature has long attracted the attention of specialists, because medicine, as an integral part of human existence, is reflected in the field of culture. Based on this, the object of this article is the medical thesaurus of a literary text, and its subject is its lexical and thematic representation. The texts of the dilogy of I. Ilf and E. Petrov were chosen as the research material, because they have not yet been systematically described in this way. The aim of the work is to identify special groups of medical vocabulary in both novels and to determine its pictorial and expressive function. The relevance of the article lies in the fact that it describes the dilogy in the context of modern medical discourse research, which is very actively developing today. The article uses descriptive and field methods. In the first case, the necessary empirical research data are identified, and in the second, they relate to each other on lexico–thematic, poetic and discursive principles. The scientific novelty of the research is the approach to medical vocabulary in dilogy from the point of view of the "poetics of medicine". It is established that in both works the vocabulary naming the external anatomical components of the human body is widely represented. Along with this, there is a vocabulary denoting bone and cavities of the body, skin and hair, secretions and fluids secreted by the body. A special place in the dilogy is occupied by the names of diseases (mental and physical), their symptoms and consequences. All this is accompanied by vocabulary representing medicines, the medical care system, and medical accessories. Based on the conducted research, it was found out that the authors of the dilogy, I. Ilf and E. Petrov, understood medical topics well both at the household and clinical level. At the same time, the medical vocabulary used by them is an integral part of the visual and expressive fabric of both novels.